Изменение реактивности организма при диафиазарных переломах костей голени в зависимости от методов лечения и его коррекция (экспериментально-клиническое исследование) - Ханапияев У.Б.; Khanapiyaev U.B. (My University, 2002)
At present investigation’s by reparative regeneration of the bone-tissue against a back-ground of the disbalance endogenous factor’s be founded of the experimental daties and the clinical observation’s (control). Inadequate studed a theoretical substation of participation specific and not-specific reaction of the immunity, biochemical and pathomorphological changes in the time of trauma and development of the autoimmunity and other immuno-pathological processes, which be able complicate the during of disease. The object of investigation’s - attribute of the changes reaction’s of organism in the time of trauma shinbone’s, raise the effective of the treatment sick’s by means of application immuno-correction’s and laserotherapia in the conditions if stabilityfunctionality osteosintesis. Our investigation consist two block’s, which include the cycle of the experimental and clinically investigation’s. The experimental investigation’s taked with help 242 of white rates of Vistarline. The morphological and biochemical investigation’s taked with help 137 rates. All animals divided on the six group. A first group composed the intactly animals, which was physiological normal control. In second group studed the dynamic appropriate a index of blood on 3, 7 and 14 twenty-four after trauma. To animals in next time’s was deed: a stability-functionality osteosynthesis of the next method’s: 1. Intramedularity osteosynthesis with help of springes. 2. On the bone osteosynthesis with of plates. 3. Knitting - apparate F 4. Bar apparate F To experimental animals was deed laserotherapia with help of the apparat «Milta» in the sphere of shin. In radiated every day 7 time, frequency of the radiation’s 1000 Hz, tensification of the magnetic bield 35 Tesia, time of work 2 minutes. The morphological investigation’s consist in reparation regeneration of the bone tissue, changes in the lymphatic gangliones, thymus and spleen with help of method’s transmission-electro-microscope (ТЕМ) and light-microscope. The biochemical changes blood’s of animals: determination of general albumen and albumen fraction’s with help of method electroforetical division on acetatecellulosical films. By 242 animals immunologically changedes. after experimental fracture, after osteosynthesis and after immunocorrection’s. Studed immunologically parameter of blood, thymus and spleen-determination of the absolute number leucocytes, relative and absolute number lymphocytes, relative and absolute number T- and B-lymphocytes, concentration of the immunoglobulines A, M, G in serum of blood, phagocytes activity of neutrophyles, micro-viscous and charge surface membrane lymphocytes. Cycle of the clinical observation’s based on the result’s of treatment 108 sick’s with a fracture bone-tissue. All sick’s divised on the on the 3 group: The first group deted immunoglobulinum after operation’s. The second group laserotherapia and mirth group deted combination - immunomodulin+laser. Immunomodulinum quarantine marked correction of the breached index’s. The laserotherapia a promote to normolization of disproteinemia and stimulate to the functionality activity leucocytes. The complex changes of laserotherapia and immunocorrection a promote to acceleration of the reparativity and immunity processe, to receipt maximally stimulate effects. This is maximally raise economic effectes for calculation of reduce fractures; reduce of time treatment of sik’c in hospital. In process of medical treatment was clinical, rentgenological, innunological and magnetic-resonant tomographical changes.
A change reaction’s of organism by the fractures shin’s in diaphys depending on methods of nedical treatment and his correction